A low leakage SRAM macro with replica cell biasing scheme. - Takeyama, Y.
For mobile applications of SRAMs, there is a need to reduce standby current leakages while keeping memory cell data. For this purpose, we propose a replica cell biasing scheme which controls the cell bias voltage by self-tuning using replica cells. This scheme minimizes the cell leakage regardless of the process fluctuations and the environmental conditions. In addition, leakage reduction in row decoder circuits is also desirable, because standby current leakages in peripheral circuits are dominated by row decoders. We also propose a row decoder circuit which can reduce both the off-leakage and the gate-leakage in the row decoders. We fabricated a 90-nm 512-Kb low-leakage SRAM macro to verify the proposed leakage reduction techniques. With these techniques, 88% reduction of the standby leakage in the sleep mode and 40% reduction of the leakage compared with the conventional diode clamp scheme are realized.
Keywords: 512 kbit; 90 nm; Cell bias voltage control; Cell leakage; Diode clamp scheme; Leakage reduction; Low leakage SRAM macro; Peripheral circuits; Replica cell biasing scheme; Row decoder circuits; Standby current leakages